Hak Waris Anak Adopsi Dari Orang Tua Yang Telah Bercerai Dalam Perspektif Hukum Perdata Barat - Karina Megawati; Ghansham Anand (Res Judicata, 2018)
Pluralism concerning stipulation of regulation regarding inheritance in Indonesia commonly stimulates numerous problems. This situation is getting complicated when it deals with regulation about adoption. Complex issue that commonly occurs within this regulation is concerning the status of adopted children when their foster parents are getting divorce. The present study aims to examine and elaborate further about civil connection between adopted children and their foster parents coupled with their inheritance rights when their parents are divorced based on western civil law point of view. The method uses in the present study is normative legal research, in which conducted it is conducted by examining the library materials or secondary law while in finding and collecting the data is done by two approaches, namely the law and conceptual approaches. The present study shows that based on Staastlaad 129:1917 it is stated that adopted children possess civil relation with their foster parents  in which the relationship is same as with their biological parents. Therefore, although their foster parents are divorced, they still hold inheritance rights from their foster father and mother. Moreover, inheritance rights that holds by adopted children is equal with the inheritance rights that is possessed by biological children.